The Evolution of Splint Armour in Georgia and Byzantium: Lamellar and Scale Armour in the 10th-12th Centuries - TSURTSUMIA, Mamuka (Byzantina Symmeikta, 2011)
Byzantine technology was part of the military technology that existed in vast areas of Eurasia; hence study of the armament of its neighbours is important.The purpose of the present paper is to add new data about Byzantium’s Caucasian neighbour (namely, Georgia). Besides that, it also includes certain views about the stages of the evolution and provenance of splint (scale and lamellar) armour. This paper also attempts to clarify the difference between banded and linear suits of lamellar armour.There is no doubt that the Byzantine military machine exercised considerable influence on its neighbours, though an opposite phenomenon can also be noticed. The article shows that changes in armour were taking place almost simultaneously in the Byzantine Empire and the Georgian kingdoms and that some of the types of armour that were widespread in Byzantium may have originated in Georgia.